PENGARUH PENERAPAN CORPORATE GOVERNANCE PADA MANAJEMEN LABA OLEH CHIEF EXECUTIVE OFFICER BARU - Narolita, Ekasari; Krisnadewi, Komang Ayu (E-Jurnal Akuntansi, 2016)
The goal in this study to determine the effect of Implementation of Corporate Governance In Profit Management By New Chief Executive Officer. This study uses a quantitative approach in the form of associative, and derived from secondary data sources. This research was conducted at a manufacturing company doing the turn of the CEO and is listed on the Stock Exchange in the period 2008-2014, the sample was taken by purposive sampling technique, in order to get a sample of 37 companies. This study uses multiple linear regression analysis technique. The analysis showed that the variables independent board and activity commissioners significant negative effect on earnings management. As for the variable size of the audit committee and the audit committee activity had no effect on earnings management.
Keywords: CEO turnover; corporate governance; earnings management; board of directors; audit committee